2022
DOI: 10.1007/s11224-022-02049-0
|View full text |Cite
|
Sign up to set email alerts
|

Computational screening for investigating the synergistic regulatory potential of drugs and phytochemicals in combination with 2-deoxy-D-glucose against SARS-CoV-2

Abstract: COVID-19 disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was declared a global pandemic by the World Health Organization (WHO) in March 2020. Since then, the SARS-CoV-2 virus has impacted millions of lives worldwide. Various preclinical and clinical trials on the treatment of COVID-19 disease have revealed that the drugs that work in combination are more likely to reduce reinfection and multi-organ failure. Considering the combination drug therapy, herein, we performed a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Drug-drug interactions (DDI) and synergistic regulatory potential have been investigated in a report describing a molecular coupling and simultaneous molecular dynamics simulation of multiligands to study the combined efect of 2-DG with other 62 selected drugs and phytochemicals. In terms of binding energy, the combination of 2-DG with Ruxolitinib, Telmisartan, and Punicalagin was superior to that of the selected individual compound [114].…”
Section: Docking and Computational Studies Covid-19mentioning
confidence: 96%
“…Drug-drug interactions (DDI) and synergistic regulatory potential have been investigated in a report describing a molecular coupling and simultaneous molecular dynamics simulation of multiligands to study the combined efect of 2-DG with other 62 selected drugs and phytochemicals. In terms of binding energy, the combination of 2-DG with Ruxolitinib, Telmisartan, and Punicalagin was superior to that of the selected individual compound [114].…”
Section: Docking and Computational Studies Covid-19mentioning
confidence: 96%
“…The cleavage site recognized by the protease appears in proteins involved in human innate immunity and may interfere with the immune response to viral infection [45]. Due to the apparent suitability of 3CL pro for drug development, a vast range of studies have included plant polyphenol-3CL pro docking, including PUN, punicalin, corilagin, chebulagic acid and geraniin, as well as EA and urolithins [93,104,[106][107][108][109][110][111][112][113][114]. The catalytic dyad of 3CL pro is composed of H41 and C145, and in silico docking showed that EA and its precursors form H-bonds with the catalytic C145 residue [104,[106][107][108]114].…”
Section: Binding Of Ellagitannins and Ellagic Acid To Components Of S...mentioning
confidence: 99%
“…The two viral proteins nsp9 and nsp10 (methyltransferase) interact with NFκB repressing factor (NKRF) and may interfere with NFκB transcription activity, for which NKRF competes [46]. Nsp15 (endonuclease) and PUN were identified as interacting in silico [110]. A more extensive screen identified punicalin as the lowest binding energy partner for RdRp (nsp12, RNA-dependent RNA polymerase), as well as for nsp9 and PL pro (nsp3, papain-like protease) [1].…”
Section: Binding Of Ellagitannins and Ellagic Acid To Components Of S...mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Drug combination therapy could exhibit synergistic efficacy and reduce resistance. 4,5 Combination therapy can also minimize harmful side effects by lowering the drug doses 6,7 (Figure 1). Pyrazoline derivatives are heterocyclic compounds that have been reported to have promising pharmacological activities against cancer cells, such as cell division inhibition and apoptosis induction.…”
Section: Introductionmentioning
confidence: 99%